The Effectiveness of Implementing the Supreme Court Ordinance Number 3 of 2022 on Electronic Mediation in Courts - Ardina Khoirun Nisa (LEGAL BRIEF, 2023)
The emergence of the Pandemic in Indonesia announced in March 2020 has impacted on the restrictions preventing crowds, including the implementation of the judiciary. To overcome the issues, the Supreme Court Ordinance Number 3 of 2022 comes into existence. This study aims to find out the provisions for electronic mediation in court based on Supreme Court Ordinance Number 3 of 2022 and to investigate whether the implementation of Supreme Court Ordinance Number 3 of 2022 has been implemented properly. This study employed normative legal research methods aimed at examining the content of positive legal norms or norms containing research subjects, which are legislation and other legal materials. The results showed that the emergence of Supreme Court Ordinance Number 3 of 2022 where the implementation of electronic mediation is established with the principles of voluntary, confidential, effective, safe, and established with the principles of voluntary, confidential, effective, safe and reachable access. In line with Chapter 1 of the Supreme Court Ordinance Number 3 of 2022, electronic mediation is a way of dispute resolution through negotiation to elicit an agreement by using recent technology. Meanwhile, the Supreme Court Ordinance Number 3 of 2022 has been implemented properly in several courts, they are the Rantauprapat Religious Court, the Magelang Religious Court, the Pinrang Religious Court of Class 1A, and the leadership council of the Pekalongan Advocate Association.